Increasing utilization of strong opioid analgesics in a UK primary care population - Zin, Che Suraya; Chen, Li-Chia; Knaggs, Roger D (2012)
Aims of investigation Studies predominantly conducted in the United States (US) have persistently reported on the increasing trends of opioid utilization which was associated with increasing incidence of dependence and misuse, higher healthcare resources and higher death rate. To date, there are limited data available about the opioid utilization in actual clinical practice in the United Kingdom (UK). This preliminary study aims to evaluate the overall utilization of strong opioid analgesics for the treatment of pain in the UK primary care setting.